Molecular Analysis of the Contribution of Alkaline Protease A and Elastase B to the Virulence of Pseudomonas aeruginosa Bloodstream Infections - Mateu-Borrás, Margalida; Zamorano, Laura; González-Alsina, Alex; Sánchez-Diener, Irina; Doménech-Sánchez, Antonio; Oliver, Antonio; Albertí, Sebastián (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomonas aeruginosa is a major cause of nosocomial bloodstream infections. This microorganism secretes two major proteases, alkaline protease A (AprA) and elastase B (LasB). Despite several in vitro studies having demonstrated that both purified proteases cleave a number of components of the immune system, their contribution to P. aeruginosa bloodstream infections in vivo remains poorly investigated. In this study, we used a set of isogenic mutants deficient in AprA, LasB or both to demonstrate that these exoproteases are sufficient to cleave the complement component C3, either soluble or deposited on the bacteria. Nonetheless, exoprotease-deficient mutants were as virulent as the wild-type strain in a murine model of systemic infection, in Caenorhabditis elegans and in Galleria mellonella. Consistently, the effect of the exoproteases on the opsonization of P. aeruginosa by C3 became evident four hours after the initial interaction of the complement with the microorganism and was not crucial to survival in blood. These results indicate that exoproteases AprA and LasB, although conferring the capacity to cleave C3, are not essential for the virulence of P. aeruginosa bloodstream infections.